2020
DOI: 10.1038/s41467-020-16158-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fate, dynamics and niches of renal macrophages of bone marrow or embryonic origins

Abstract: Renal macrophages (RMs) participate in tissue homeostasis, inflammation and repair. RMs consist of embryo-derived (EMRMs) and bone marrow-derived RMs (BMRMs), but the fate, dynamics, replenishment, functions and metabolic states of these two RM populations remain unclear. Here we investigate and characterize RMs at different ages by conditionally labeling and ablating RMs populations in several transgenic lines. We find that RMs expand and mature in parallel with renal growth after birth, and are mainly derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 81 publications
(185 reference statements)
4
69
2
Order By: Relevance
“…Supportively, a large-scale single-cell transcriptomic analysis of viral antigen-reactive CD4 + T cells from 32 patients with COVID-19 showed increased proportions of cytotoxic follicular helper cells and cytotoxic T-helper cells (CD4-CTLs) responding to SARS-CoV-2 in patients with severe disease compared with those with mild disease ( 31 ). This model may be a useful tool to dissect the role of these cells in the pathogenesis of COVID-19 using our recently established cell ablation models ( 32 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supportively, a large-scale single-cell transcriptomic analysis of viral antigen-reactive CD4 + T cells from 32 patients with COVID-19 showed increased proportions of cytotoxic follicular helper cells and cytotoxic T-helper cells (CD4-CTLs) responding to SARS-CoV-2 in patients with severe disease compared with those with mild disease ( 31 ). This model may be a useful tool to dissect the role of these cells in the pathogenesis of COVID-19 using our recently established cell ablation models ( 32 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the authors showed that a significant portion of kidney resident macrophages were originated from adult HSC derived monocytes. Liu and colleagues also demonstrated that both lineages of resident macrophages shared the feature of longlived residency in the kidney, but had functional differences in aspects including immune response and metabolic profile in disease conditions (18). These data suggest that kidney resident macrophages can be derived from multiple precursor populations and that their ontological origin may influence their function (6,17,18).…”
Section: Macrophages In Kidneymentioning
confidence: 97%
“…The idea that resident macrophages are a homogenous population in the kidney and are exclusively derived from embryonic precursors has recently been challenged as well. Utilizing a newly generated cre-induced-hCD59 transgenic line, Liu and colleagues traced the fate of resident macrophages in the kidney from birth to full maturity and found that a portion of resident macrophages are actually derived from peripheral monocytes (18). The idea that some kidney resident macrophages are derived from monocytes was supported by data from Ms4a3 Cre -Rosa TdT fate-mapping mice that faithfully label all adult hematopoietic stem cell (HSC) derived monocytes (19).…”
Section: Macrophages In Kidneymentioning
confidence: 99%
“…CXCL17 attracts professional antigen presenting cells 40 , including macrophages, through its receptor CXCR8. Very little is known about the role of CXCL17 in the kidney but single-cell RNA sequencing analysis revealed that CXCL17 expression is enhanced at an early time point in murine tubulointerstitial fibrosis model 37 . CX3CL1, which binds to CX3CR1, plays a major role in the recruitment of resident macrophage during kidney development 41 and may increase renal macrophage abundance by prolonging their survival 42 . CX3CL1 has also been shown to support renal monocytes recruitment in the context of renal injury and CX3CL1/CX3CR1 inhibition has been generally shown to reduce renal fibrosis in different models of renal injury 43-45 . LGALS9, a mammalian -galactoside binding lectin, was first isolated from murine embryonic kidney 46 .…”
Section: Discussionmentioning
confidence: 99%
“…CX3CL1, which binds to CX3CR1, plays a major role in the recruitment of resident macrophage during kidney development 41 and may increase renal macrophage abundance by prolonging their survival 42 . CX3CL1 has also been shown to support renal monocytes recruitment in the context of renal injury and CX3CL1/CX3CR1 inhibition has been generally shown to reduce renal fibrosis in different models of renal injury 4345 .…”
Section: Discussionmentioning
confidence: 99%